2021
DOI: 10.1002/mp.15358
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation success rate of repetitive‐pulse focused ultrasound in an in vivo giant axon model: An acoustic parametric study

Abstract: Purpose: Focused ultrasound (FUS) is a promising tool to develop new modalities of therapeutic neurostimulation. The ability of FUS to stimulate the nervous system,in a noninvasive and spatiotemporally precise manner,has been demonstrated in animals and human subjects, but the underlying biomechanisms are not fully understood yet. The objective of the present study was to investigate the bioeffects involved in the generation of trains of action potentials (APs) by repetitive-pulse FUS stimuli in a simple inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Previous research in both animal and human experiments has explored objective measures, including action potentials, evoked electroencephalographic responses, and tactile sensations experienced by subjects during FUS stimulation, to validate the efficacy of FUS. However, specific objective parameters or biomarkers capable of confirming the results after FUS treatment in patients with neuropathic pain remain unidentified [55,56,67]. Consequently, the assessment of FUS effects relied solely on the patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in both animal and human experiments has explored objective measures, including action potentials, evoked electroencephalographic responses, and tactile sensations experienced by subjects during FUS stimulation, to validate the efficacy of FUS. However, specific objective parameters or biomarkers capable of confirming the results after FUS treatment in patients with neuropathic pain remain unidentified [55,56,67]. Consequently, the assessment of FUS effects relied solely on the patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another more accessible model preparation is the giant axon system of the earthworm. One study found that FUS application to the giant fibers of the nerve cord was effective in eliciting trains of action potentials; however, this effect was mentioned to be indirect and likely via FUS stimulation of afferent input ( Vion-Bailly et al, 2019 , 2022 ). Another group reported an FUS-induced reduction in action potential amplitude and conduction velocity following sonication, and although a second group, who targeted the medial and lateral giant fibers, could replicate this reduction in action potential amplitude, they did not observe a decrease in conduction velocity ( Yoo et al, 2017 ).…”
Section: Focused Ultrasound Effect Directionmentioning
confidence: 99%
“…In recognition of the limitations in their respective intact neural systems, FUS neuromodulation researchers investigating mechanisms of action have applied their efforts to pared down systems, typically cultured mammalian neurons ( Rinaldi et al, 1991 ; Mihran et al, 1996 ; Prieto et al, 2018 ; Qiu et al, 2019 ), mammalian slice preparations ( Rinaldi et al, 1991 ; Bachtold et al, 1998 ; Tyler et al, 2008 ; Muratore et al, 2009 ), or tractable invertebrate models ( Wahab et al, 2012 ; Wright et al, 2015 ; Zhou et al, 2017 ; Kubanek et al, 2018 ; Lin et al, 2019 ; Vion-Bailly et al, 2019 , 2022 ; Dedola et al, 2020 ). Isolation in culture is known to alter the intrinsic electrical properties of neurons ( Turrigiano et al, 1994 ); FUS effects on cultured cells may thus differ from outcomes in intact systems.…”
Section: The Single-cell Approachmentioning
confidence: 99%